2014
DOI: 10.18632/oncotarget.2769
|View full text |Cite
|
Sign up to set email alerts
|

Wnt signaling, de novo lipogenesis, adipogenesis and ectopic fat

Abstract: Wnt signaling is as a major regulator of adipogenesis. It differentially regulates the fate of mesenchymal stem cells (MSC) by promoting osteogenesis and myogenesis, and inhibiting adipogenesis[1]. Its loss of function has been associated with impaired osteogenesis[2] and diverse congenital and adult cardiovascular disorders[3,4]. Our group has identified loss of function mutations in Wnt coreceptor LRP6 that underlie autosomal dominant early onset coronary artery (CAD), osteoporosis and most features of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
12
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 13 publications
2
12
0
1
Order By: Relevance
“…Our results suggest β-catenin signaling could inhibit adipogenesis through downregulation of C/EBPα and PPARγ expression. Recently, β-catenin has been shown to block interaction between the T-cell factor/lymphoid enhancer-binding factor (TCF/LEF)-binding domain of β-catenin and the catenin-binding domain of C/EBPα and PPARγ [8][9][10]. These studies, suggesting β-catenin as upstream regulator of C/EBPα -PPARγ pathways support our results.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our results suggest β-catenin signaling could inhibit adipogenesis through downregulation of C/EBPα and PPARγ expression. Recently, β-catenin has been shown to block interaction between the T-cell factor/lymphoid enhancer-binding factor (TCF/LEF)-binding domain of β-catenin and the catenin-binding domain of C/EBPα and PPARγ [8][9][10]. These studies, suggesting β-catenin as upstream regulator of C/EBPα -PPARγ pathways support our results.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, increasing evidences suggest that β-catenin inhibit adipogenesis by blocking interaction between the TCF/LEF-binding domain of β-catenin and the catenin-binding domain of C/EBPα/and PPARγ. In addition, in the nucleus, β-catenin upregulates its target gene cyclin D1 (CCND1), which downregulates key adipogenic transcription factors, C/EBPα and PPARγ [8][9][10]. Therefore, upregulation of β-catenin pathway could be considered as effective target signaling in inhibiting adipogenesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence revealed that activation of Wnt/b-catenin signaling inhibited the differentiation and lipogenesis in 3T3-L1 adipocytes [6]. Another study demonstrated that Wnt signaling was critically involved in de novo lipogenesis and adipogenesis in nonalcoholic fatty liver disease [7]. These emerging data give the possibility that the Wnt/b-catenin signaling could regulate the adipogenic phenotype of HSCs.…”
mentioning
confidence: 96%
“…Este hecho no se ha descrito previamente y está en desacuerdo con resultados de Risbud. Aunque CSM-NP en ambos documentos compartieron los mismos marcadores inmunofenotípicos, ligeras diferencias en el método de diferenciación o la fuente de NP, junto con el hecho de que en nuestros discos de trabajo se encontraban en un estado de degeneración más avanzada, puede dar cuenta de esta alteración en la diferenciación adipogénica.En estos estados de degeneración discal, la vía de regulación adipogénica Wnt puede actuar como un importante regulador e inhibir la diferenciación de MSC a adipocitos[222] . La activación de la señalización de la vía Wnt, inhibe la adipogénesis parda de células cultivadas, al impedir la inducción de los factores de transcripción PPAR y C/EBP[223] .Se ha identificado un mediador en esta vía, el Wnt10b como un potente inhibidor de la adipogénesis, que debe ser suprimido in vitro para poder diferenciar adipocitos[224,225] .…”
unclassified